2010
DOI: 10.1016/j.jpedsurg.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an artificial alveolar-capillary membrane: a novel continuously perfused model within microchannels

Abstract: Introduction-Pulmonary hypoplasia is a condition of the newborn that is characterized by underdeveloped lungs and poor outcome. One strategy in the treatment of patients with hypoplasia is to augment underdeveloped lungs using biocompatible artificial lung tissue. However, one central challenge in current pulmonary tissue engineering efforts remains the development of a stable biomimetic alveolar-capillary membrane. Accordingly, we have built a series of bio-mimetic microfluidic devices that specifically model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…To this end, several strategies have been used in an attempt to enhance vascularization in TE muscle. The first method utilizes bioengineered scaffolds that have been designed to incorporate “channels” for the supply of nutrients to the regenerating tissue [38,39]. In a second approach, angiogenic growth factors are linked to a scaffold in order to entice the infiltration of host ECs into the regenerating tissue [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several strategies have been used in an attempt to enhance vascularization in TE muscle. The first method utilizes bioengineered scaffolds that have been designed to incorporate “channels” for the supply of nutrients to the regenerating tissue [38,39]. In a second approach, angiogenic growth factors are linked to a scaffold in order to entice the infiltration of host ECs into the regenerating tissue [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The system also allowed for testing of cellular responses to mechanical changes in sheer stress by altering the flow rate through the channels. This revealed that cells exposed to high flow rates and thus higher sheer stress levels had decreased proliferation when compared with cells exposed to low flow (Nalayanda et al 2010). Carraro and colleagues used MEMS photolithographic and etching protocols to create a patterned template that can be used to mould silicone wafers with a vascular-type branching pattern.…”
Section: Nanoscale Surface Patterningmentioning
confidence: 96%
“…For a comprehensive overview on such models, readers are referred to the recent t 4 report by Gordon and colleagues (2015). Until recently, only a few MPS trying to emulate functional parts of the lung have been developed (Nalayanda et al, 2007; Nalayanda et al, 2010), but in 2010, a microphysiological lung-on-a-chip system developed by Donald Ingber’s group at the Wyss Institute for Biologically Inspired Engineering at Harvard University Boston, MA, USA, made it for the first time into Science Magazine (Huh et al, 2010). Figure 7a shows the design and principles of this system which is mimicking the function of a lung alveola.…”
Section: Microphysiological Systems – An Expanding Toolbox For Hazmentioning
confidence: 99%